Case Reports of Enamel Microabrasion Associated with At-home Dental Bleaching After Orthodontic Bracket Removal - Pavani, C. C. [UNESP] (2021)
Adequate removal of residual bonded materials from the enamel surface after orthodontic bracket debonding is critical, since any remaining composite may compromise enamel surface morphology and esthetics. The following clinical case reports present the association of at-home dental bleaching using 10% carbamide peroxide and the removal of residual bonded material using a super fine, tapered diamond bur followed by the use of an enamel microabrasion product after orthodontic bracket debonding. The proposed treatment considerably improved the esthetics and successfully removed the grooves created during the removal of the bonding composite, resulting in a smooth enamel surface.